2009
DOI: 10.1099/ijs.0.008243-0
|View full text |Cite
|
Sign up to set email alerts
|

Haloterrigena jeotgali sp. nov., an extremely halophilic archaeon from salt-fermented food

Abstract: A novel red-pigmented halophilic archaeon, strain A29T , was isolated from shrimp jeotgal, a traditional salt-fermented food from Korea. This strain grows in the ranges 10-30 % (w/v) NaCl, 17-50 6C and pH 6.5-8.5, with optimal growth occurring at 15-20 % NaCl, 37-45 6C and pH 7.0-7.5. The isolate is Gram-negative and non-motile. Phylogenetic analysis, based on 16S rRNA gene sequences, showed that strain A29 T is associated with the genus Haloterrigena and closely related to the species Haloterrigena thermotole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 36 publications
0
21
0
Order By: Relevance
“…Halophilic archaea isolated from Korean foods using culture-dependent methods include Haladaptatus cibarius [44], Halalkalicoccus jeotgali [47], Halorubrum cibi [42], Haloterrigena jeotgali [45], and Natronococcus jeotgali [46] from various types of jeotgals, and also Halogranum salarium [23] from bay salt. Their characteristics are shown in Table 1.…”
Section: Halophilic Archaea In Korean Foodsmentioning
confidence: 99%
“…Halophilic archaea isolated from Korean foods using culture-dependent methods include Haladaptatus cibarius [44], Halalkalicoccus jeotgali [47], Halorubrum cibi [42], Haloterrigena jeotgali [45], and Natronococcus jeotgali [46] from various types of jeotgals, and also Halogranum salarium [23] from bay salt. Their characteristics are shown in Table 1.…”
Section: Halophilic Archaea In Korean Foodsmentioning
confidence: 99%
“…In fact, several strains of haloarchaea were isolated from fish sauce: Halobacterium salinarum and Halococcus sp., which reach their maximum densities after 3 or 4 weeks. Moreover, new species, such as Natrinema gari, have been isolated from fish sauce (Tapingkae et al, 2008), Natronococcus jeotgali and Halalkalicoccus jeotgali from other foods, such as shrimp jeotgal (Roh et al, 2007 a,b), and Halobacterium piscisalsi, and Halorubrum cibi from fermented fish (Yachai et al, 2008;Roh et al, 2009).…”
Section: Uses In Fermented Foodsmentioning
confidence: 99%
“…Previous studies have shown that there are differences in the polar lipid composition among species of the two genera. Haloterrigena species contain the glycolipids S 2 -DGD (Cui et al, 2006;Gutiérrez et al, 2008;MontalvoRodríguez et al, 2000;Roh et al, 2009;Ventosa et al, 1999;Xu et al, 2005b) or mannose-6-sulfate (1A2)-glucose glycerol diether (S-DGD) (Romano et al, 2007), but most Natrinema species have phosphatidylglycerol sulfate and unidentified glycolipids (McGenity et al, 1998; Tapingkae (Kumar et al, 2004). Bootstrap values (%) are based on 1000 replicates and are shown for branches with more than 70 % bootstrap support.…”
Section: Strain Jx313mentioning
confidence: 99%
“…salina (Gutiérrez et al, 2008) and Htg. jeotgali (Roh et al, 2009). In this study, an aerobic haloalkaliphilic archaeon designated strain JX313 T was isolated.…”
mentioning
confidence: 99%